2003
DOI: 10.1023/a:1024175325850
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Adriamycin widely used in the treatment of neoplastic conditions is nephrotoxic. In the present study the protective effect of lipoic acid was investigated in adriamycin-induced nephrotoxicity in adult male albino Wistar rats. Adriamycin-induced nephrotoxicity was characterized by hyperlipidemia, proteinuria, and hypoproteinemia, by decreased activities of the enzymes N-acetyl-beta-D-glucosaminidase and cathepsin D, by increased lipid peroxidation and decreases in serum catalase and glutathione activities, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…This improvement was consistent with Moini et al [61] and Kang et al, [62] who found that ALA has antioxidant, anti-inflammatory, and antiapop-totic effects. A similar study was reported by Malarkodi et al, [63] who demonstrated the influence of lipoic acid on DOX-induced nephrotoxicity, but the model is completely different from our study in ALA dose and treatment duration (35 mg/kg intraperitoneally once a week for 12 weeks) as well as the chronic model of Dox-induced nephrotoxicity using DOX in a dose of 1 mg/kg i.v. once a week for 12 weeks where inflammatory and apoptotic biomarkers were not assessed.…”
Section: Discussionsupporting
confidence: 55%
“…This improvement was consistent with Moini et al [61] and Kang et al, [62] who found that ALA has antioxidant, anti-inflammatory, and antiapop-totic effects. A similar study was reported by Malarkodi et al, [63] who demonstrated the influence of lipoic acid on DOX-induced nephrotoxicity, but the model is completely different from our study in ALA dose and treatment duration (35 mg/kg intraperitoneally once a week for 12 weeks) as well as the chronic model of Dox-induced nephrotoxicity using DOX in a dose of 1 mg/kg i.v. once a week for 12 weeks where inflammatory and apoptotic biomarkers were not assessed.…”
Section: Discussionsupporting
confidence: 55%
“…When combined with traditional CVRF such as hypertension, hyperlipidaemia and diabetes, the protective effect of STAT3 will be weakened, making the myocardium more vulnerable to injury (Ferdinandy et al, 2014). In addition, lipid metabolism may indirectly increase the risk of ASCVD (Malarkodi et al, 2003). Therefore, ASCVD risk assessment should be actively given early in breast cancer patients, especially postmenopausal breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%